Customer value in polish e-commerce sector - Kabut, Mateusz; Komorowska, Magdalena (Funkcjonowanie e-biznesu. Zasoby, procesy, technologie, 2015)
Why some companies succeed and others go bankrupt? Many practitioners and researchers have been looking for answer to this question for decades. Currently many believes that some part of the answer lays in the business models which are used by companies. It is claimed that the value proposition which is offered to the customers is a key element of each business model.Due to dynamic globalization processes and rapid development of new ICT technologies, it might be expected that the value propositions of the companies are going to become similar to each other. This phenomena shall be observable especially within e-businesses. Unfortunately there are only few researches addressing this issue.Therefore the main objective of this article is to present outcomes of research that was conducted on polish e-commerce companies. We found that polish Web-based shops may be not so concerned about price as it is believed.